Superabsorbing Metasurfaces with Hybrid Ag–Au Nanostructures for Surface‐Enhanced Raman Spectroscopy Sensing of Drugs and Chemicals. Issue 7 (7th May 2018) - Gao, Jun; Zhang, Nan; Ji, Dengxin; Song, Haomin; Liu, Youhai; Zhou, Lyu; Sun, Zhi; Jornet, Josep M.; Thompson, Alexis C.; Collins, R. Lorraine; Song, Yun; Jiang, Suhua; et al.
Abstract: Reliability, shelf time, and uniformity are major challenges for most metallic nanostructures for surface‐enhanced Raman spectroscopy (SERS). Due to the randomness of the localized field supported by silver and gold nanopatterns in conventional structures, the quantitative analysis of the target in the practical application of SERS sensing is a challenge. Here, a superabsorbing metasurface with hybrid Ag–Au nanostructures is proposed. A two‐step process of deposition plus subsequent thermal annealing is developed to shrink the gap among the metallic nanoparticles with no top‐down lithography technology involved. Because of the light trapping strategy enabled by the hybrid Ag–Au metasurface structure, the excitation laser energy can be localized at the edges of the nanoparticles more efficiently, resulting in enhanced sensing resolution. Intriguingly, because more hot spots are excited over a given area with higher density of small nanoparticles, the spatial distribution of the localized field is more uniform, resulting in superior performance for potential quantitative sensing of drugs (i.e., cocaine) and chemicals (i.e., molecules with thiol groups in this report). Furthermore, the final coating of the second Au nanoparticle layer improves the reliability of the chip, which is demonstrated effective after 12 month shelf time in an ambient storage environment. Abstract : Reliability, shelf time, and uniformity are major challenges for most metallic nanostructures for surface‐enhanced Raman spectroscopy (SERS). A three‐layered superabsorber structure with hybrid Ag–Au nanoparticles as the top layer is reported. The relative standard deviation of Raman intensities from this metasurface is below 6%. The sensitive sensing performance is still active after 12 month shelf time in an ambient storage environment.